Comparative Study of The Clinical Outcomes of Surgical Techniques in Lumbar Spinal Stenosis: Decompression with or without Instrumentation - علي, محمد; محفوض, مفيد; عبد الرحمن, يامن (Latakia University Journal -Medical Sciences Series, 2020)
AIM: The primary aim is to compare laminotomy versus laminectomy plus instrumentation in lumbar spinal stenosis treatment regarding low back pain -radicular pain- muscular weakness and claudication distance after surgery on discharge and after three months of surgery and the secondary objective is to compare complications between the two surgical techniques. Methods: a 42 consecutive patients had been studied where laminotomy was done in 25 patients (where bilateral laminotomies were done with foraminotomies with preservation of the spinal process and supra and intraspinal ligaments) and decompression with instrumentation were done in 17 patients, low back pain and radicular pain had been assessed using visual analogue scale (VAS) and the functional status was assessed using oswestry disability scale (ODI) and muscle strength was assessed using the medical research council strength scale both on discharge and after the surgery by three months. Results: in laminotomy group there were 25 patients 13 female and 12 males the median age was 59 years, in the instrumentation group there were 17 patients the mean age was 58.05 with 13 females and 4 males and by comparing results we found that back pain improvement was better in laminotomy alone (p=0.03) and radicular pain improvement was better for decompression with instrumentation (p=0.0468), there were no statistical difference regarding ODI (p=0.511), incidental durotomy (p=0.342) or urinary tract infection (p=0.1406).